2016
DOI: 10.5606/archrheumatol.2016.5938
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Nephrolithiasis Among Patients With Ankylosing Spondylitis: a Population-Based Cohort Study

Abstract: Objectives: This study aims to investigate the correlation of ankylosing spondylitis (AS) with nephrolithiasis by performing a nationwide populationbased cohort study. Patients and methods:The data used in this retrospective cohort study were collected from the Taiwan National Health Insurance Research database. The study included a total of 3,334 AS patients (1,914 males, 1,420 females; mean age 44.51±16.83 years; range 22 to 79 years) and 13,336 non-AS patients (7,656 males, 5,680 females; mean age 44.27±17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The percentages of newly diagnosed nephrolithiasis were 5.76% in AS and 4.58% in the non-AS patients. The results showed that patients with AS were more likely to be associated with nephrolithiasis than non-AS patients [14].…”
mentioning
confidence: 93%
“…The percentages of newly diagnosed nephrolithiasis were 5.76% in AS and 4.58% in the non-AS patients. The results showed that patients with AS were more likely to be associated with nephrolithiasis than non-AS patients [14].…”
mentioning
confidence: 93%